Severe maternal sepsis in the UK, 2011–2012: A national case-control study - Acosta, CD; Kurinczuk, JJ; Lucas, DN; Tuffnell, DJ; Sellers, S; Knight, M (Public Library of Science, 2014)
Background In light of increasing rates and severity of sepsis worldwide, this study aimed to estimate the incidence of, and describe the causative organisms, sources of infection, and risk factors for, severe maternal sepsis in the UK.